MANAJEMEN MATERIAL PADA PROYEK KONSTRUKSI JEMBATAN BETON, STUDI KASUS JEMBATAN BETON MERIAN DESA KUMPANG ILONG, KECAMATAN BELITANG HULU KABUPATEN SEKADAU - Rumano, Plasidus; ., Rafie; Pratiwi, Riyanni (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
Construction projects in the field of civil engineering, particularly concrete bridge project is complex and involves a lot of merging and combining resources are diverse, so it requires a material management plan specifically can manage materials in construction projects. The use of the material in the bridge construction project is one of the most important parts that have a fairly large percentage of the total cost of the project , therefore the use of good management techniques and appropriate materials to buy , store, distribute and count the use of construction materials becomes very important . Material issues that often occur in the implementation of the bridge project is delays in ordering materials as well as materials come how the storage process, including planning for material storage warehouse. As for the purpose of this penelititian among others, be able to identify the material on the concrete bridge projects, designing schedule the use of materials, designing organizational structures that takes care of materials management, designing the process of ordering and delivery of materials and material storage plan on concrete bridge construction projec. As for the results of research , among others can be found with the format of materials management at the concrete bridge construction project Merian Ilong tainted village will be easier to determine work priorities based materials handling procedures have been arranged systematically , material scheduling is the first step in starting the process of management material that will facilitate the processes contained in the materials management , weather factors ( climate ) priority in determining when a material delivery process is done . Â Keywords : Management of Materials, Concrete Bridge , Belitang Hulu District, SekadauRegency